Liposuction: Nursing Considerations and Perioperative Care - Sharahili, Ameena Abdu Nasheb; Dahma Ahmed Ahmed Bakri; Norah Turki Hakami; Layla Abdul Haq Abdul Algafoor Mostafa; Wafa Kamiyhan SH Alanazi; Jehan Ahmad Almurab; Manal Abdu Mohammed Zidan; Merfat Mohammed ali ALsaeed; Latifah Abdulaziz Mohammed Alqahtani; Ghala Haylan Bin Libdh; Amani Abdullah Hassan Oribi; Amal ALahmari (Saudi Journal of Medicine and Public Health, 2025)
<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Background:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Liposuction is one of the most commonly performed cosmetic surgical procedures worldwide, primarily aimed at body contouring through the removal of localized subcutaneous fat deposits. Advances in surgical techniques, equipment, and perioperative care have significantly improved patient safety and aesthetic outcomes, increasing the role of nurses and interprofessional teams in achieving optimal results. <span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Aim:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> This article aims to review liposuction with a specific focus on nursing considerations, perioperative care, patient selection, procedural techniques, possible complications, and the role of the interprofessional healthcare team in ensuring patient safety and recovery. <span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Methods:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> A narrative review approach was used to synthesize current principles of liposuction practice. The article examines anatomical foundations, indications and contraindications, equipment, operative techniques, and perioperative nursing responsibilities based on established clinical guidelines and published evidence. <span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Results:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Proper patient selection, knowledge of subcutaneous fat anatomy, careful technique, and modern equipment contribute to safe and effective liposuction outcomes. Nursing interventions, including preoperative education, intraoperative monitoring, postoperative surveillance, early ambulation, and patient counseling, play a critical role in minimizing complications such as contour deformities, thromboembolism, and local anesthetic toxicity. <span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Conclusion:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Liposuction is a safe and effective body-contouring procedure when performed with meticulous surgical planning and comprehensive nursing care. Interprofessional collaboration and vigilant perioperative monitoring are essential to reduce complications and enhance patient satisfaction.